Selection of salt-tolerant wheat genotypes for better yield considering physio-biochemical attributes and antioxidative defence potential: agronomic traits and stress tolerance indices - Muhammad Akram; Qasim Ali; Shafaqat Ali; Mohamed A. El-Sheikh; Pallab K. Sarker (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science)
Different approaches are being employed, including selection through breeding for high yielding salt-tolerant wheat genotypes to overcome the negative impacts of salinity for better production. Experiment was conducted in sand filled pots with 24 newly developed wheat inbreed lines and two parental genotypes, using 200 mM NaCl salinity level. Genotype specific decline found in yield related and agronomic characteristics. Nonetheless, the degree of changes in physio-biochemical processes was genotype-specific. Genotypes SB1, SB4, SB10, SB16, SB20, SB22 and SB24 performed better in grain yield-related attributes, associated with better maintenance of leaf photosynthetic pigments, less lipid peroxidation and better antioxidative defence mechanism. Grain yield reduction in SB1, SB4, SB10, SB16, SB20, SB22 and SB24 was 39.540%, 43.902%, 35.778%, 44.444%, 40.716%, 39.778% and 39.361%, respectively and maximum % yield reductions recorded in lines SB2 (54.250), SB7 (57.170), SB14 (57.289), SB15 (54.814), SB19 (56.674), SB21 (61.431) and SB23 (54.940). Heat map analysis, PCA and correlation studies performed to determine the relative stress tolerance of wheat genotypes under study to corroborate the findings of stress tolerance indices (STIs). conclusively, physio-biochemical processes, in addition to agronomic qualities, morphological characteristics and STIs, should considered crucial for selecting salt tolerant wheat genotypes for improved yield through breeding.